Alkali chloride doped SnO2 electron-transporting layers for boosting charge transfer and passivating defects in all-inorganic CsPbBr3 perovskite solar cells. Issue 26 (25th June 2021) - Xie, Guixiang; Lu, Xiaochun; Duan, Jialong; Dong, Yan; Jiang, Xiurong; Tu, Fengzhang; Duan, Yanyan; Tang, Qunwei
Abstract : An electron-transporting layer (ETL) with improved charge extraction-transfer kinetics and a perovskite film with improved quality highly determine the power conversion efficiency (PCE) of perovskite solar cells (PSCs). Abstract : An electron-transporting layer (ETL) with improved charge extraction-transfer kinetics and a perovskite film with improved quality highly determine the power conversion efficiency (PCE) of perovskite solar cells (PSCs). Herein, various alkali chlorides (MCl, M = Li, Na, K, Rb and Cs) are employed as passivators to simultaneously modulate the electronic properties of the underlying SnO2 ETL and to regulate the quality of the upper all-inorganic CsPbBr3 perovskite film. The primary results demonstrate that the detrimental oxygen vacancies at the SnO2 surface and under-coordinated Pb 2+ in the perovskite film are counterbalanced by alkali chlorides, benefiting the PCE promotion of the carbon electrode based CsPbBr3 PSC. Because of the accelerated charge extraction, the reduced defects and the suppressed nonradiative recombination, the best device free of encapsulation tailored by the SnO2 –RbCl ETL achieves a champion PCE as high as 10.04% with improved long-term stability under 80% relative humidity over 15 days, which is much higher than the 7.88% for the reference device. The proposed strategy demonstrates great promise for the development of highly-efficient PSCs with a defect engineering related concept.